On the 50th anniversary of the Scientific Research Company “Electron-Carat” - Mykola Vakiv (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The article is dedicated to the Scientific Research Company "Electron-Carat", which was founded in 1972 as the Lviv Research and Development Institute of Materials - the leading developer of the state-of-art materials. Nowadays, the SRC "Electron-Carat" is leading industrial institution of Ukrainian specialized on search, investigation, technological development and small-scale production of materials for functional electronics, in particular nano-, micro-, opto-, acoustic-, cryo-, magneto- and quantum electronics. The SRC "Electron-Carat" is a certified scientific organization included in the state register. Some of the company's laboratories have been recognized as national heritage of Ukraine. The main scientific and technological scope of SRC "Electron-Carat" includes production of single-crystal epitaxial layers of complex oxides using the liquid-phase epitaxy method; production of epitaxial semiconductor structures based on A3B5 compounds by MOCVD and liquid-phase epitaxy methods; precision mechanical processing of single-crystal materials; vacuum deposition of metal and dielectric coatings; property research and parameter control of materials; production of silicon wafers; manufacture of electronic components based on ceramic and thick-film technologies.